Decline in nominal construction volume expected for the first time since the financial crisis: Residential construction situation worsening - Martin Gornig; Laura Pagenhardt (DIW Weekly Report, 2024)
High construction prices and worsened financing conditions are weighing on the construction industry, especially build-ing construction. Despite a nominal increase of six percent in construction expenses in 2023, it decreased by just over one percent in inflation-adjusted terms. In 2024, the nominal construction volume is likely to contract by around 3.5 percent, declining for the first time since the financial crisis due to falling construction prices. Residential construction in particular experienced a sharp decline in 2023 and will continue on this downward trend more strongly in 2024. Renovation and modernization activity is less affected than new construction. The situation will stabilize by 2025. The prospect of constructing 400,000 new residences annually is thus becoming increasingly out of reach. Only civil engineering is stabilizing the construction industry overall; it is likely to expand in both 2024 and 2025. The different growth prospects of the sectors require restructuring in the construction industry. In particular, capacities freed up in new residential construction should be utilized in the energy-efficient renovation of private and public buildings. Policy makers should actively support this restructuring. In addition, they should provide clarity about the subsidy programs for energy-efficient building renovation and residential unit construction. At the same time, it is important to maintain focus on the new housing construction target.
Keywords: E32; E66; 330; Construction industry; residential construction; public infrastructure; economic outlook